Reconstruction of the Long Process of the Incus by Use of Glass Ionomer Cement: Our Experience - Ali, Khaled Abd El Rahman; Ibrahim, Maha Ahmed; Hussien, Mohammed Ahmed; Dahy, Khaled Gamal (International Archives of Otorhinolaryngology, 2022)
Introduction Chronic suppurative otitis media is one of the most common causes of reversible conductive hearing loss which can lead to necrosis of the ossicles. The incus, especially its long process, is the most common ossicle affected.Objectives The present study aims to assess the use of glass ionomer cement for the reconstruction of the long process of the incus.Methods The present study was conducted on 27 patients with chronic suppurative otitis media with central perforation with dry and quiescent ears with an eroded long process of the incus submitted to tympanoplasty. The audiological evaluations were done on all patients, including preoperative and postoperative evaluation of the air-bone gap; the average pure tone threshold was done 6 months postoperatively.Results The average air pure tone threshold was 42.8 dB preoperatively and 22.5 dB postoperatively. The postoperative air pure tone thresholds were significantly smaller than the preoperative values (p < 0.01). The air-bone gap was 30.5 dB at 500 Hz, 31.6 dB at 1 KHz, and 24.1 dB at 2 kHz preoperatively, and 7.7 dB at 500 Hz, 7.2 dB at 1 KHz, and 7.1 dB at 2 kHz postoperatively at the end of 6 months of follow-up. There were significant hearing gains in the air-bone gap (p < 0.001).Conclusion Glass ionomer cement is a useful and effective material for bridging the defect of the long process of the incus.
Keywords: glass ionomer cement; hearing loss; ossiculoplasty; audiometry